Growth and Development of Acanthiophilus helianthi (Diptera: Tephritidae) Feeding on Safflower, Carthamus tinctorius - Karim SAEIDI; Shahram MIRFAKHRAEI; Fariba MEHRKHOU (Notulae Scientia Biologicae, 2015)
Safflower fly, Acanthiophilus helianthi Rossi (Diptera: Tephritidae), undergoes four stages (egg, larva, pupa and adult) during its growth and development. In this study, observation showed that the egg’s stage took 1.16 ± 0.00, larva’s stage took 12.02 ± 0.13 and pupa’s stage took 7.03 ± 0.08 days before the emergence of adults. The male adult survived for 21.97 ± 2.69 days, while the female lived 19.19 ± 1.50 days. It was observed that the eggs were laid in a cluster, with a range between 10 – 50 eggs per cluster. The length and width of the individual egg were 1.12 ± 0.03 mm and 0.20 ± 0.00 mm respectively. The percentages of the survived individual larva decreased from the first instar until third instar. In the experiment, the length and width of the larva reached 7.77 ± 0.08 mm and 1.84 ± 0.03 mm respectively. Pupae were observed changing in colour from pale white to dark brown. The length and the width of the pupae observed were 6.78 ± 0.16 mm and 2.90 ± 0.02 mm. The longevity of the adults Acanthiophilus helianthi Rossi was influenced by the diets they consumed, the presence of other individuals, wideness of the areas, differences in time taken within the life cycle (between different stages) and temperature in the laboratory.